Delayed Bronchiolitis Epidemic in French Primary Care Setting Driven by Respiratory Syncytial Virus: Preliminary Data from the Oursyn Study, March 2021. Issue 12 (December 2021) - Rybak, Alexis; Levy, Corinne; Jung, Camille; Béchet, Stéphane; Batard, Christophe; Hassid, Frédéric; Zouari, Morched; Cahn-Sellem, Fabienne; Bangert, Mathieu; Cohen, Robert
Abstract : We report early results from a prospective primary care bronchiolitis surveillance study in France in which a 10-week delayed epidemic was detected from February to March 2021. Among 225 children under 2 years with swab testing for a first bronchiolitis episode, 55% had a positive test for RSV, 0 for influenza, and 1 for severe acute respiratory syndrome coronavirus 2. Abstract : Supplemental Digital Content is available in the text.